The role of the National Bank of Ukraine in the state financial monitoring - Kazansky, Maxim (My University, 2014)
The problem of legalization (laundering) of illegal profit and terrorist financing arises globally and concerns international community. Проблема легалізації (відмиванню) незаконних прибутків та фінансуванням тероризму в усьому світі і виникає стурбованості міжнародної спільноти.
Keywords: National Bank; financial monitoring; legalization; Національний банк; фінансовий моніторинг; легалізація; Национальный банк; финансовый мониторинг; легализация